PENGGUNAAN APLIKASI CANVA DALAM PRAKTEK PEMBUATAN MARKETING TOOLS PADA MATA KULIAH HOTEL MARKETING. - Nirwani, Ayulia; Syahlevie, Nor (Jurnal Perhotelan dan Pariwisata, 2024)
Abstract This research examines the Canva application's use in creating marketing tools in the Hotel Marketing course. The study's main objective is to evaluate the effectiveness of Canva as a learning tool in improving students' skills in designing marketing materials such as business cards, brochures, and company profiles for the hospitality industry. This study employs a classroom action research method, involving 54 hospitality program students from a polytechnic in Indonesia. Participants were divided into an experimental group using Canva and a control group using traditional methods. Data were collected through observation, interviews, assessment of the quality of marketing tools produced, student’s confidence and quality in roleplay activities. The results show that students who performed roleplays using self-made promotional media demonstrated better material mastery and confidence than those who performed roleplays without promotional media. These findings highlight the potential of Canva as an effective pedagogical tool in hospitality education. This learning approach can equip students with basic visual design skills relevant to modern industry demands. This research provides valuable insights for hospitality educators in integrating design technology into the curriculum to enhance student learning outcomes. Keywords: canva, hotel marketing, marketing tools, classroom action research